Shock Wave Dispersion in Fluids with Loosely Distributed Rigid Bodies - de Krasiński, J.S.; Khosla, A.; Ramesh, V. (Engineering Transactions, 1977)
G.I. TAYLOR'S [1,5] probabilistic approach to blast waves in turbulent air is extended for shock waves propagating through randomly distributed solids in gas. The shock wave suffers dispersion and is changed to a train of weak waves spread over a longer positive time duration. If frictional tosses are small, the impulse remains approximately constant and the standard deviation of the attenuated wave has been found to be of the form [equasion].This is for baffles with randomly aligned perforations. A similar expression has been found for granulated materials in gas. The constants A, B and h have been experimentally determined. The above expression for standard deviation has been maximized with respect to the inverse of void fraction of granules. Thus for thickness of baffles of 0.178 cms, y = 1.18 and for an equivalent diameter of granules of 0.068 cms, y = 4.1 for maximum dispersion. Frictional losses neglected in this study have been dealt with by the authors in a different paper [8].